Radiomics in Oncology: A 10-Year Bibliometric Analysis - Ding, Haoran; Wu, Chenzhou; Liao, Nailin; Zhan, Qi; Sun, Weize; Huang, Yingzhao; Jiang, Zhou; Li, Yi (Frontiers in Oncology, 2021)
Objectives: To date, radiomics has been applied in oncology for over a decade and has shown great progress. We used bibliometric analysis to analyze the publications of radiomics in oncology to clearly illustrate the current situation and future trends and encourage more researchers to participate in radiomics research in oncology. Methods: Publications for radiomics in oncology were downloaded from the Web of Science Core Collection (WoSCC). Data on WoSCC was collected, and CiteSpace was used for bibliometric analysis on countries, institutions, journals, authors, keywords, and references involved in this field. The researching situation and hotspots were analyzed through burst detections. Results: A total of 7199 pieces of literature were analyzed on CiteSpace concerning radiomics in oncology. The number of publications showed rapid growth and continues to boom. The United States and Chinese Academy of Sciences were found to be the most prolific country and institution, respectively. In terms of journals and co-cited journals, Scientific Reports was ranked highest with respect to the number of publications, and Radiology ranked highest in co-cited journals. Moreover, Jie Tian had the maximum number of publications, and Phillipe Lambin was the most cited author. A paper published by Gillies et al. showed the highest citation counts. Artificial intelligence (AI), segmentation method, and use of radiomics for classification and diagnosis in oncology were hotspots in this field. The test-retest, statistics, which means reproducibility and statistical method of radiomics research, the relation between genomics and radiomics, and the applications of radiomics in sarcoma and intensity-modulated radiotherapy were the research frontiers. Conclusion: To our knowledge, this is the first study to provide an overview of literature related to radiomics in oncology, which may inspire researchers from multiple disciplines to engage in radiomics-related research.